FACTORS AFFECTING CORRUPTION IN LOCAL GOVERNMENT IN EAST JAVA PROVINCE BASED ON THE FRAUD TRIANGLE THEORY - Bodroweni Bodroweni; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2025)
This study aims to examine the influence of good governance, audit objectivity and independence, and technology on fraud prevention at the Central Java Province Representative Office of the Audit Board of Indonesia. Based on the Performance Report of the Central Java Province BPK Representative for the year 2023, it is noted that on the indicator of Control Fulfillment and Trust in Audit Quality, there was a 40% decrease in realization in 2023 compared to 2022 with a realization of 98.11% and 2021 with a realization of 86.22%. Then, on the indicator of Information Technology Utilization, in 2023 it only reached a realization of 83.90% compared to 96.21% in 2022 and 99.18% in 2021This research was conducted using a quantitative method with a population consisting of all auditors at the BPK Representative Office of Central Java Province, using a saturated sampling technique totaling 125 auditors. The data collection method used a questionnaire with a weighted Likert scale of 1-5. The data in this study were analyzed using the multiple linear regression analysis method with the analysis tool being SPSS 29.0.The research results show that good governance has a significantly positive impact on fraud prevention, audit objectivity and independence have a significantly positive impact on fraud prevention, and technology has a significantly positive impact on fraud prevention. The findings of this research indicate that the better the governance implemented in the Central Java Province BPK Representative, the better the fraud prevention will be accepted; the better the objectivity and independence of the audit applied by the auditors in the Central Java Province BPK Representative, the better the fraud prevention will be accepted; and the more advanced the technology used in the Central Java Province BPK Representative, the better the fraud prevention will be accepted.